DOP04 Inflammatory Bowel Disease (IBD) and Solid Organ Transplantation. Natural history of pre-existing and de novo IBD patients. (EITOS study of GETECCU). (21st January 2022) - Bastón Rey, I; Calvino Suárez, C; Luque, A M; Caballol, B; Soutullo, C; Bravo, A; Castaño, A; Gros, B; Bernal, L; Diz Lois, M T; Alonso Galán, H; Cañete, F; et al.
Abstract: Background: Limited data is available of the outcome of inflammatory bowel disease (IBD) in patients with solid organ transplantation (SOT). The aim of our study was to describe the natural history of pre-existing IBD and de novo IBD after SOT. Methods: A retrospective, observational, multi-centre, nationwide study was designed. IBD patients with SOT were included. We identified two separate cohorts: (1) patients with pre-existing IBD at the time of SOT and (2) patients without IBD at the time of SOT (de novo IBD). The primary outcome was IBD progression, defined by the escalation of medical treatment, surgical therapy for medically refractory IBD or IBD-related hospitalization during follow-up. Risk factors were identified using multivariate Cox proportional hazard analysis. Results: A total of 177 patients (106 pre-existing IBD and 71 de novo IBD) from 31 centres were included. Baseline characteristics are shown in Table 1. Eighty-six patients with IBD and SOT underwent liver transplantation, while 82 required renal, 4 lung, 3 heart, 1 liver/kidney and 1 pancreas/kidney transplantation. Pre-existing IBD patients were followed-up over a median of 4.8 years (range 2.6–9.4). At the time of SOT, 61 patients (59.8%) were not under maintenance treatment or were treated with 5-aminosalicylates, 10 (9.8%) were on immunosuppressive therapy and 31 (30.4%) were receiving biological agents, of which 8 were on combo therapy. At the moment of SOT, only 8 patients (7.5%) had moderate IBD activity whereas the remaining patients were in remission. During follow-up 33.7% of patients with pre-existing IBD had disease progression, with a median time between SOT and IBD progression of 2.2 years (range 1.3–4.6). No differences between Crohn′s disease and ulcerative colitis were found (Figure 1). The median time of follow-up in de novo IBD group was 5.1 years (range 2.1–8.2). In this cohort, 55.9% of patients had disease progression during follow-up (Figure 2), with a median time to flare of 1.9 years (range 0.8–3.9) from diagnosis. In pre-existing IBD cohort, multivariate Cox-regression analysis identified active IBD at the time of SOT (HR=1.80; 95%CI: 1.14–2.84; p=0.012) and the presence of extraintestinal manifestations (HR=3.10; 95%CI: 1.47–6.54; p=0.003) as predictive factors of IBD progression after SOT. Conclusion: One third of patients with pre-existing IBD have disease progression, needing medical therapy escalation, surgery or hospitalization after SOT. Active IBD at the time of SOT and the presence of extraintestinal manifestations were identified as risk factors for disease progression. In de novo IBD cohort, about half of patients showed disease progression during follow-up.